Human Adipose-Derived Stromal Cells for Cell-Based Therapies in the Treatment of Systemic Sclerosis. Issue 5 (May 2013) - Scuderi, Nicolò; Ceccarelli, Simona; Onesti, Maria Giuseppina; Fioramonti, Paolo; Guidi, Chiara; Romano, Ferdinando; Frati, Luigi; Angeloni, Antonio; Marchese, Cinzia
The present study was designed to evaluate the clinical outcome of cell-based therapy with cultured adipose-derived stromal cells (ASCs) for the treatment of cutaneous manifestations in patients affected by systemic sclerosis (SSc). ASCs have an extraordinary developmental plasticity, including the ability to undergo multilineage differentiation and self-renewal. Moreover, ASCs can be easily harvested from small volumes of liposuction aspirate, showing great in vitro viability and proliferation rate. Here we isolated, characterized, and expanded ASCs, assessing both their mesenchymal origin and their capability to differentiate towards the adipogenic, osteogenic, and chondrogenic lineage. We developed an effective method for ASCs transplantation into sclerodermic patients by means of a hyaluronic acid (HA) solution, which allowed us to achieve precise structural modifications. ASCs were isolated from subcutaneous adipose tissue of six sclerodermic patients and cultured in a chemical-defined medium before autologous transplantation to restore skin sequelae. The results indicated that transplantation of a combination of ASCs in HA solution determined a significant improvement in tightening of the skin without complications such as anechoic areas, fat necrosis, or infections, thus suggesting that ASCs are a potentially valuable source of cells for skin therapy in rare diseases such as SSc and generally in skin disorders.